Penerapan Metode Make A Match dalam Pembelajaran PAI untuk Meningkatkan Hasil Belajar Siswa di Kelas IV SDN 39 Pasar Gompong - Zurlaini Zurlaini (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study discusses the application of the Make A Match method in PAI learning in class IV SD Negeri 39 Pasar Gompong on the material of recognizing the names of Angels and their duties. The background of this research is the low interest of students in learning so that methods are needed that can make students more active in learning activities. The formulation of research problems includes: 1) how is the application of Make A Match method in PAI learning, and 2) how are the students' learning outcomes after the application of the method. The type of research used is class action research (PTK). The Make A Match method was applied in two cycles, in the form of a game to find pairs of cards held by students, thus encouraging students to be active, work together, and understand the material. The results showed an improvement in the process and learning outcomes. Student learning activities in cycle I were in the good category, increasing to very good in cycle II. The average pre-test score was 36.875 with 12.5% completeness, increased in the first cycle post-test to 66.25 with 56.25% completeness, and in the second cycle post-test to 85.625 with 75% completeness.